LEGAL CONSEQUENCES OF DIFFERENCES IN LIMITED LIABILITY COMPANY DATA IN NOTARIAL DEEDS AND COMPANY REGISTERS - Muhammand Adam Hafiza (Jurnal Ilmiah Advokasi, 2024)
Notaries have an important role in a limited liability company because they are notaries is an official who has the authority to make deeds in a Limited Liability Company at the same time is the sole proxy of the prospective founder or the proxy of the Company's directors in the process ratification of legal entities, approval of changes to the articles of association and also notification changes to the articles of association and/or Limited Liability Company data as well as information notifications others electronically on the Legal Entity Administration System (SABH). organized by the Directorate General of General Legal Administration (Ditjen AHU) on Ministry of Law and Human Rights of the Republic of Indonesia. In practice, It is possible that company data contained in the Company Register at SABH is available differences in data with notarial deeds. This can happen due to inaccuracy notary when filling in company data at SABH and not carefully checking suitability of a company's data in notarial deeds and company register. As is Differences in company data can give rise to legal disputes and significant losses arise later if the company's data is not corrected, which will be experienced by the founders, shareholders of Limited Liability Companies and notaries. From these Legal issues arise regarding the Validity of Company Data in the event that there are differences between Notarial Deed and Company Register and regarding Liability for Differences Company Data in Notarial Deed and Company Register. This research is research normative law, using a statutory approach, and a conceptual approach.Keywords: Company Register; Deed; Legal Administration System; Limited Liability Company; Notary